Der Erzbergbau in Nordmanitoba/Kanada - Entwicklung und gegenwärtiger Stand - Metz, Bernhard; Rogge, John R. (ERDKUNDE, 1976)
This paper reviews the development of the mining indus try in northern Manitoba. In particular, it focuses upon the dramatic expansion over the past twenty years, during which time the industry has grown from virtual insignificance to become one of the major metallic mineral producing areas in Canada. The nickel industry in the Thompson region is the most important activity, but a number of other areas - at Flin Flon, Snow Lake, Lynn Lake and Leaf Rapids - are also important for their copper and zinc production. A consequence of the industry's growth has been the concomitant expansion of settlement into the hitherto non-ecumene of the subarctic. Moreover,the mining industry has diversified the Province's economic base and thereby reduced its traditional dependence upon agriculture-related activities.